S28 Increased Incidence of COPD Exacerbations Following Influenza Vaccination. (19th November 2012) - Donaldson, GC; Kowlessar, BS; Patel, ARC; Mackay, AJ; Singh, R; Brill, S; Wedzicha, JA
Abstract : Introduction: Influenza vaccination prevents substantial morbidity, and mortality, and the spread of infection, but patients still sometimes refuse vaccinations due to concerns over adverse reactions. Our aim was to determine the relative risk of COPD exacerbations post-vaccination. Methods: We analysed data before and after 162 vaccinations given to 112 patients in the London COPD cohort between 2009 and 2011. Patients recorded on daily diary cards increase in respiratory symptoms. Exacerbations were defined as ≥2 days of 2 major symptoms (new or increased breathlessness, sputum volume or purulence) or 1 major and 1 minor symptom (cold, increased cough, increased wheeze, sore throat). Patients were telephoned in Oct 2011 and asked about recent or forthcoming vaccinations; other dates were known from previous years when recorded diary cards or reported at clinic visits. The risk of COPD exacerbation in the two post-vaccination periods, days 1–2 and 3–14 were calculated relative to the patient's baseline risk assessed over the year before and after vaccination using a self-controlled case series approach. The data was also simply analysed with a Chi-squared test of the proportion of exacerbations in the two weeks before and after vaccination. Results: There was a 3.31 fold (95% CI 1.5–7.4; P=0.004) increased risk of COPD exacerbation 1–2 days post influenza vaccination, and a 1.8 fold risk (1.2–2.9; p=0.007) 3–14 days afterwards. In the two weeks prior to vaccination there were 5/162 exacerbations and 26/162 in the two weeks post vaccination (p<0.001). All 5 of the exacerbations before and 17/26 exacerbations after vaccination were treated with antibiotics and/or oral steroids. Using thie healthcare utilisation definition of COPD exacerbations, there were still significantly more events post vaccination (p=0.008). Figure 1 shows the average number of new or increased respiratory symptoms recorded by the patients during the 3 weeks before and after vaccination. Conclusion: The incidence of COPD exacerbation increases immediately after influenza vaccination. COPD patients should be warned about increased respiratory symptoms after their influenza vaccination. Future studies should investigate the mechanisms underlying these increased symptoms in order to intervene and prevent them effectively.